Potential Use of Helicteres isora L. in Diabetes Mellitus: A Systematic Review of Scientific Literature - Saravanan, Kamatchi Sundara; Gowri, Radhakrishnan; Ramesh, Karthik Kumar; Shetty, Sanjana; Maity, Soubhagya (Pharmacognosy Communications)
Introduction: Plant-based medicines have been in use over the years for the management and treatment of various ailments including diabetes. The current study was undertaken to explore and compile the research evidence on Helicteres isora L. (Sterculiaceae) in the management of diabetes. Materials and Methods: Peer-reviewed literature was retrieved during January 2023 from databases comprising of PubMed, Science Direct, Springer and LILACS. The obtained literature was initially subjected to title and abstract screening, followed by full-text screening. Results: The study includes 12 articles that were chosen among a total of 111 articles retrieved through various sources. The selected articles reported either in vitro assay or in vivo evaluation of various extracts of H. isora bark, fruit, or root for its anti-diabetic property. The duration of the in vivo evaluation studies were up to 30 days in Wistar rat/Swiss albino mice/C57BL mice. The diabetogenic agents used were either Streptozotocin (STZ) or alloxan, while the reference drugs used comprised of tolbutamide, pioglitazone, glibenclamide, insulin, or metformin. A significant anti-diabetic property of various parts of H. isora were reported in the reviewed studies. Conclusion: The available evidence demonstrates the potential of H. isora against diabetes as it holds significant glucose-lowering effects in the reported screened models. Bioactivity-guided fractionation followed by elucidation of the mechanism of action will be useful in establishing the application of the plant species in diabetes.
Keywords: Helicteres isora; Diabetes; Root; Bark; Fruit